WORK MEASUREMENT STUDY ON MOTOR-MANUAL PINE TAPPING OPERATION: THE APPLICATION OF THE CONCEPT OF LEAN MANUFACTURING AND ALLOWANCES - Yuliati Yovi, Efi; Prasetiana, Diah; Aquilla Nirmalasari, Natasha (Association of Indonesian Forestry and Environment Researchers and Technicians, 2021)
Derivated products of pine resin have been recognised as competitive commodities in global trade, increasing the need to use resources more efficiently. A hand-held tapping machine with small hoe-shape cutters called “mujitek” has been widely applied in Indonesia among efforts to answer this challenge. In this study, a series of observed (actual) work time data were measured and analysed, adopting lean manufacturing to calculate the basic and standard time of the work and estimate the work produced on the tapping operation. Work elements were identified based on their contribution to change or transform the product and were categorised as value-added, non-value-added, and special allowance. Quantitative data on the work productivity in the tapping operation can be used as one fundamental data in determining a work plan to establish a continuous improvement process. The variable fatigue allowances taken into account in this study were standing posture, abnormal posture, muscular energy, atmospheric conditions, and noise. This study shows that non-value-added work elements (repairing machines, chatting, and smoking) cause inefficiency in tapping operation. Analysis of added-value work elements proved that this hand-held tapping machine offers a higher (1.7 times) work productivity than conventional hand-held tapping tools. However, since humans have limitations in the physical, physiological, and mental dimensions that limit their ability to carry out work at a certain level, the discovered work productivity level should also be validated with other thresholds, e.g., physical workload and risk perception.